2010
DOI: 10.1039/c001674h
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable transportation based on electric vehicle concepts: a brief overview

Abstract: The energy storage system is of decisive importance for all types of electric vehicles, in contrast to the case of vehicles powered by a conventional fossil fuel or bio-fuel based internal combustion engine. Two major alternatives exist and need to be discussed: on the one hand, there is the possibility of electrical energy storage using batteries, whilst on the other hand there is the storage of energy in chemical form as hydrogen and the application of a fuel cell as energy converter. The advantages and limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
196
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(205 citation statements)
references
References 3 publications
0
196
0
2
Order By: Relevance
“…30,[34][35][36] During the 2000s, research in the field increased, 7,37 as governments and industry showed increased interest in the development of PEMFCs for powering automotives. 38 In their widely cited review paper from 2005, Gasteiger et al quantified the improvements required to the activity of Pt to enable the commercialisation of automotives running on PEMFCs. 7 According to their measurements, state-of-the-art carbon-supported pure Pt nanoparticles exhibited a mass activity of 0.16 A mg Pt À1 at U ¼ 0.9 V with respect to a reversible hydrogen electrode (RHE).…”
Section: Ulrik Grønbjergmentioning
confidence: 99%
“…30,[34][35][36] During the 2000s, research in the field increased, 7,37 as governments and industry showed increased interest in the development of PEMFCs for powering automotives. 38 In their widely cited review paper from 2005, Gasteiger et al quantified the improvements required to the activity of Pt to enable the commercialisation of automotives running on PEMFCs. 7 According to their measurements, state-of-the-art carbon-supported pure Pt nanoparticles exhibited a mass activity of 0.16 A mg Pt À1 at U ¼ 0.9 V with respect to a reversible hydrogen electrode (RHE).…”
Section: Ulrik Grønbjergmentioning
confidence: 99%
“…In addition, CO in lower amounts (o10 ppm) may be tolerant by the anode catalysts, and then several basic strategies had been suggested for this case: (i) high temperature operating, (ii) air or O 2 bleeding, (iii) potential/current pulsing, and (iv) advanced alloy catalysts. [4][5][6][7][8][9] However, they generally encounter some problems, e.g., long-term stability, safety issues, setup complexity, and system efficiency. Thus it is of importance to get insight into CO poisoning and its resulted dynamic properties (e.g., poisoning, reactivating and oscillations) in PEMFCs so as to provide a practical guide to industrial and automotive applications.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] The main challenge in the utilization of H 2 -based PEMFCs is the manufacture, storage, and transport of extremely pure hydrogen (499.999%) as an ideal fuel for PEMFCs. Thus the alternative H 2 -rich reformates, produced by the off-board steam reforming, partial oxidation or autothermal reforming of light hydrocarbons and alcohols [7][8][9][10][11] would be attractive and promising fuels for PEMFCs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, electric vehicles (EV) historically predate gasoline vehicles, but have only received significant interest in the last decade (see Eberle and Helmot (2010) for an overview).…”
Section: Introductionmentioning
confidence: 99%